If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -2 = 5x + -9 Reorder the terms: -2 + 7x = 5x + -9 Reorder the terms: -2 + 7x = -9 + 5x Solving -2 + 7x = -9 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -2 + 7x + -5x = -9 + 5x + -5x Combine like terms: 7x + -5x = 2x -2 + 2x = -9 + 5x + -5x Combine like terms: 5x + -5x = 0 -2 + 2x = -9 + 0 -2 + 2x = -9 Add '2' to each side of the equation. -2 + 2 + 2x = -9 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = -9 + 2 2x = -9 + 2 Combine like terms: -9 + 2 = -7 2x = -7 Divide each side by '2'. x = -3.5 Simplifying x = -3.5
| f(12)=.25(12-3) | | 8x-1=11x-9 | | 2-u=6 | | -5(1+6X)-8x=38+5x | | 4=2u-2 | | 4i/9-6i | | 0.5p=3.5 | | -x+17+3x+17=-4 | | 3+4y=9 | | 0.25w=16 | | -6k+3=-7-(6k-8) | | 2=2m-2 | | 4x(2x+9)-2(5x+6)= | | 7x+4-3+5-3x= | | 3x-11=-2x-7 | | -16=3-5n+1 | | 18y=6 | | 2*(1200/x) | | 6/m-3 | | 3j-2=14 | | x-6.25=2.5 | | -28x-7y=28 | | 7x+4y-3x+4= | | 13+x(x-13)-(2-5x)=2.8 | | 15d+7=8d+56 | | 19-x=2 | | 3+4j=11 | | -10=-4a-6a | | 3.4=6c-8 | | 2+2r=4 | | 6-2x-1=13 | | 1=5-2t |